2007
DOI: 10.1161/circulationaha.107.704890
|View full text |Cite
|
Sign up to set email alerts
|

Atrium-Selective Sodium Channel Block as a Strategy for Suppression of Atrial Fibrillation

Abstract: Our study demonstrates important differences in the inactivation characteristics of atrial versus ventricular sodium channels and a striking atrial selectivity for the action of ranolazine to produce use-dependent block of sodium channels, leading to suppression of AF. Our results point to atrium-selective sodium channel block as a novel strategy for the management of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
308
7
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(330 citation statements)
references
References 30 publications
14
308
7
1
Order By: Relevance
“…This is consistent with its ventricular effects through inhibition of the late inward sodium current I Na while possessing greater potency in modulating peak I Na in atrial cardiomyocytes 23. Increased late I Na leads to Ca 2+ overload through Na/Ca exchange in the reverse mode, leading with that way in electrophysiologic instability with action potential duration prolongation, early afterdepolarizations, and delayed afterdepolarizations 24, 25.…”
Section: Discussionsupporting
confidence: 71%
“…This is consistent with its ventricular effects through inhibition of the late inward sodium current I Na while possessing greater potency in modulating peak I Na in atrial cardiomyocytes 23. Increased late I Na leads to Ca 2+ overload through Na/Ca exchange in the reverse mode, leading with that way in electrophysiologic instability with action potential duration prolongation, early afterdepolarizations, and delayed afterdepolarizations 24, 25.…”
Section: Discussionsupporting
confidence: 71%
“…Accordingly, atrial selective peak I Na inhibition would be an attractive approach. In light of this, it has been shown that ranolazine acts as an atrial selective peak I Na inhibitor without possible adverse effects on ventricular electrophysiology due to consequences of peak I Na inhibition [3]. Furthermore, in a recent study, we could demonstrate that ranolazine inhibits peak and late sodium current in isolated human atrial myocytes [5].…”
Section: Discussionmentioning
confidence: 95%
“…Ranolazine has been proposed to exert inhibitory effects on atrial sodium channel parameters as well as on the delayed rectifier potassium current (I Kr ) slightly prolonging the atrial action potential [3]. This probably explains an increased effective refractory period (to a greater extent than in the ventricle) and prolonged atrial conduction time in a frequency-dependent manner in the porcine heart [4].…”
Section: Discussionmentioning
confidence: 99%
“…Atrial-selective inhibition of sodium channels has previously been demonstrated for several antiarrhythmic agents (Burashnikov et al 2007;Sicouri et al 2010) and represents a property likely contributing to dronedarone's antiarrhythmic effect. Atrial sodium channel blockade leads to alterations of various biophysical parameters of sodium current (I Na ) that produce post-repolarization refractoriness without a major effect on action potential duration (APD).…”
mentioning
confidence: 93%